Monitoring of chimerism following allogeneic haematopoietic stem cell transplantation (HSCT): Technical recommendations for the use of Short Tandem Repeat (STR) based techniques, on behalf of the United Kingdom National External Quality Assessment Service for Leucocyte Immunophenotyping Chimerism Working Group. (22nd August 2014) - Clark, Jordan R.; Scott, Stuart D.; Jack, Andrea L.; Lee, Helena; Mason, Joanne; Carter, Geoffrey I.; Pearce, Laurence; Jackson, Tony; Clouston, Hazel; Sproul, Anne; Keen, Leigh; Molloy, Karen; et al.
Summary Analysis of short tandem repeats (STR) is the predominant method for post‐transplant monitoring of donor engraftment. It can enable early detection of disease relapse, level of engraftment and provide useful information on the graft‐versus‐host disease (GVHD)/graft‐versus‐tumour (GVT) effect, facilitating therapeutic intervention. Harmonization and standardization of techniques and result interpretation is essential to reduce the impact of laboratory variability on both clinical management and the results of multi‐centre clinical trials. However, the United Kingdom National External Quality Assessment Service for Leucocyte Immunophenotyping (UK NEQAS LI) has highlighted significant issues inherent in STR testing that impact upon inter‐ and intra‐ laboratory variation. We present here consensus best practice guidelines and recommendations for STR chimerism testing, data interpretation and reporting that have been drawn up and agreed by a consortium of 11 UK and Eire clinical laboratories. This document uses data obtained from the UK NEQAS LI Post‐Stem Cell Transplant (SCT) Chimerism Monitoring Programme.